Depth-dependent photodegradation of marine dissolved organic matter - Timko, Stephen A.; Maydanov, Anastasia; Pittelli, Sandra L.; Conte, Maureen H.; Cooper, William J.; Koch, Boris P.; Schmitt-Kopplin, Philippe; Gonsior, Michael (Frontiers in Marine Science, 2015)
Marine dissolved organic matter (DOM) in surface and deep waters of the eastern Atlantic Ocean and Sargasso Sea was analyzed by excitation emission matrix (EEM) fluorescence spectroscopy and parallel factor analysis (PARAFAC). Photo-degradation with semi-continuous monitoring of EEMs and absorbance spectra was used to measure the photo-degradation kinetics and changes of the PARAFAC components in a depth profile of DOM at the Bermuda Atlantic Time Series (BATS) station in the Sargasso Sea. A five component model was fit to the EEMs, which included traditional terrestrial-like, marine-like, and protein-like components. Terrestrial-like components showed the expected high photo-reactivity, but surprisingly, the traditional marine-like peak showed slight photo-production in surface waters, which may account for its prevalence in marine systems. Surface waters were depleted in photo-labile components while protein-like fluorescent components were enriched, consistent with previous studies. Ultra-high resolution mass spectrometry detected unique aliphatic compounds in the surface waters at the BATS site, which may be photo-produced or photo-stable. Principle component and canonical analysis showed strong correlations between relative contributions of unsaturated/aromatic molecular formulas and depth, with aliphatic compounds more prevalent in surface waters and aromatic compounds in deep waters. Strong correlations were seen between these aromatic compounds and humic-like fluorescent components. The rapid photo-degradation of the deep-sea fluorescent DOM in addition to the surface water relative depletion of aromatic compounds suggests that deep-sea fluorescent DOM is very unlikely to survive overturning circulation.